Efektifitas Metode ABC (Activity Based Costing) Dalam Analisis Perencanaan Obat JKN di Puskesmas Dagangan Kabupaten Madiun - Edy Bachrun (Jurnal Kesehatan, 2017)
Drug expenditure absorbs most of the health care budget. PHC was responsible for ensuring the used of available resources optimally aimed at achieving efficiency in cost control. Based on LPLPO at Dagangan health care 2015 showed an average supply of drugs JKN in primar health care Dagangan has excess stock that is as much as 93.18% (41) types of drugs than 100% (44) types of drugs. The purpose of this research was to determine the application of the ABC method in planning analysis of drugs in Dagangan health care Dagangan Madiun city. The design of this research was descriptive categorical, with a retrospective approach. Primary data obtained from interview with Head of Health Centre and Head of Installation Pharmacy in Primary Health Care Dagangan while the secondary data obtained from LPLPO. The results showed that Dagangan health care use consumption method to planning the drug. By using the ABC analysis showed a group of JKN drugs that include into group A as many as 8 types of drugs (18,2%). Group B as many as 30 types of drugs (68,2%). And group C as much as 6 types of drugs (13,6%). Based on these results, Dagangan health care need to apply ABC analysis method to determine the priority drugs that need to be held, and there should be education and training for pharmacy personnel to increase knowledge about effective methods of drug design and efficient use of the budget.